Preliminary validation of the Portuguese Edinburgh Handedness Inventory in an adult sample - Espírito-Santo, Helena (2020)
The Edinburgh Handedness Inventory (EHI) is persistently the most used inventory to evaluate handedness, being neuropsychological investigation and clinical practice. Despite this, there is no information on how this instrument functions in a Portuguese population. The objective of this study was therefore to examine the sociodemographic influences on handedness and establish psychometric properties of the EHI in a Portuguese sample. The sample consisted of 342 adults (157 men and 185 women), assessed with a battery of neuropsychological tests. The mean EHI Laterality Quotient was 63.52 (SD = 38.00). A much high percentage of ambiguous-handedness compared to left-handedness was detected. An inconsistency was found between the preference for formal education activities (writing-drawing-using scissors) and the remaining EHI activities. From sociodemographic variables, only age, area, and regions of residence showed significant influence on EHI scores. The reliability and temporal reliability of EHI were adequate. Confirmatory factor analysis indicated a one-factor model (χ2/df = 2.141; TLI = 0.972; CFI = 0.979; RMSEA = 0.058). The inconsistency between formal education and nonformal activities could be an indicator of social pressure. The present data give support for the notion that handedness measured by EHI is potentially sensitive to sociodemographic and cultural influences.